Redes de (re)conhecimento: o impacto da introdução das novas tecnologias na gestão escolar - Mota, Maria Eloísa (2019)
In recent decades, the debate on the information society and knowledge management has been widely discussed. This research aims at investigating the impact of technologies on the pedagogical management, investigating how this new modality affects the work of the pedagogical coordinator in São Paulo city. A qualitative methodology was applied with semistructured interviews and open questions. The research subjects are pedagogical coordinators working at various schools in São Paulo city. The data interpretation occurred through the narrative analysis of the interviewed coordinators whose experiences, once articulated, showed elements of a pedagogical action undergoing changes under the impact of a digital network system. In the conceptualization of the system, the interviewees consider the articulation of all the structures for the composition of an organic totality. The data analyzed show that the Pedagogical Management System had repercussions on the coordinator’s work with several already consolidated educational activities. An efficient network system could leverage other educational actions and imply a quality advancement in teaching learning